Laws, Statutes, Ordinances, and Constitutions 11 (John Holt ed., 1763) - (:unkn) unknown (My University, 1763)
A Law for the Better Preventing of Fire, no. 4, § 6: Prohibited the discharge of firearms within the city of New York
Keywords: DISCHARGE